2019
DOI: 10.1186/s12940-019-0481-7
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to arsenic in utero is associated with various types of DNA damage and micronuclei in newborns: a birth cohort study

Abstract: Background Growing evidence indicates that in utero arsenic exposures in humans may increase the risk of adverse health effects and development of diseases later in life. This study aimed to evaluate potential health risks of in utero arsenic exposure on genetic damage in newborns in relation to maternal arsenic exposure. Methods A total of 205 pregnant women residing in arsenic-contaminated areas in Hanam province, Vietnam, were recruited. Prenatal arsenic exposure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…We used a combination of genetic and pharmacological approaches to demonstrate in vivo that oxidative stress is the initiating cause of arsenic poisoning in a tissue specific manner [54]. The absence of murine p21 induction is interesting in the light of the evidence that iAs exposure has the capacity to induce DNA damage in exposed infants [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a combination of genetic and pharmacological approaches to demonstrate in vivo that oxidative stress is the initiating cause of arsenic poisoning in a tissue specific manner [54]. The absence of murine p21 induction is interesting in the light of the evidence that iAs exposure has the capacity to induce DNA damage in exposed infants [44].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have linked arsenic exposure in utero and in adults to oxidative DNA damage [10,44]. This can result in toxicity by apoptosis mediated by the p53 pathway [45][46][47].…”
Section: Effect Of Arsenic Exposure On Ho-1 and P21 Reporter Expressionmentioning
confidence: 99%
“…The results also suggested that increased exposure to iAs alters the proportion of metabolites in urine. 9,24,36,37 Arsenic exposure linked to changes in gene expression patterns in cells or populations. 17,19,20,38 Studies had shown that iAs could change the expression of apoptosis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…First, 8-Hydroxy-2-deoxyguanosine (8-OHdG), a form of reactive oxygen species (ROS) and a major form of oxidative DNA damage, was obtained from urine and skin tissue of arsenic exposed individuals [27]. Early genetic effects including DNA strand breaks, micronuclei in cord blood, and nitrative DNA damage were found in arsenic exposed patients [28]. In addition, oxidative damages and mitochondrial mutations might play a role in arsenic-induced skin malignancies [29,30].…”
Section: Pathophysiological Mechanisms Of Arsenic-induced Carcinogmentioning
confidence: 99%